2001
DOI: 10.1074/jbc.m105607200
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a Dioxin Receptor Mutant That Is a Constitutive Activator of Transcription

Abstract: The intracellular dioxin (aryl hydrocarbon) receptor is a ligand-activated transcription factor that mediates the adaptive and toxic responses to environmental pollutants such as 2,3,7,8-tetrachlorodibenzo-p-dioxin and structurally related congeners. Whereas the ligand-free receptor is characterized by its association with the molecular chaperone hsp90, exposure to ligand initiates a multistep activation process involving nuclear translocation, dissociation from the hsp90 complex, and dimerization with its par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…The AhR mutant constitutively localizes to the nucleus, heterodimerizes with ARNT, and activates transcription by binding XRE sequences in a ligand-independent manner (29,30). The results of the present study demonstrate that AhR activation in T-lineage cells alone directly induces the thymocyte changes.…”
supporting
confidence: 53%
“…The AhR mutant constitutively localizes to the nucleus, heterodimerizes with ARNT, and activates transcription by binding XRE sequences in a ligand-independent manner (29,30). The results of the present study demonstrate that AhR activation in T-lineage cells alone directly induces the thymocyte changes.…”
supporting
confidence: 53%
“…1b)). The observed deficient Hsp90 binding to the AhR⌬PASB likely explains the previously observed constitutive activity of this construct in AhR transformation and nuclear translocation (17).…”
Section: Hsp90mentioning
confidence: 72%
“…Deletion of the ligand binding PASB domain (amino acids 287-422) generates an active (ligand-independent) AhR that constitutively dimerizes with Arnt, binds to DNA, is capable of nuclear translocation, and activates gene transcription (17) despite the fact that it retains one Hsp90 binding site (in the bHLH domain). These observations raise the question whether the Hsp90-mediated inhibitory effect on AhR transformation is binding site dependent (e.g.…”
Section: Hsp90mentioning
confidence: 99%
“…3 In a related, separate study involving mice that express a constitutively active form of AHR in the liver, investigators also observed increased hepatic Fgf21 expression (13). However, this constitutively active form of AHR was previously determined to exhibit AHR activity similar to high-dose TCDD exposure (24). Data obtained using high-dose treatments are often hard to interpret due to acute toxicity and AHR-independent effects on metabolism (1,25).…”
Section: Discussionmentioning
confidence: 92%